Development of Cultivation Technology for the Escherichia Coli Recombinant Strain Producing Arginine Deiminase of Mycoplasma Hominis - Fayura, L.R.; Boretsky, Yu.R.; Pynyaha, Yu.V.; Martynyuk, N.B.; Skorohod, V.V.; Sybirny, A.A. (Science and Innovation, 2024)
The Escherichia coli recombinant strain producing arginine deiminase of Mycoplasma hominis has been designed. Storage conditions that provide stabilization of most productive clones of the producer were found. Terms for cultivation of the arginine deiminase producer using bioreactors of different volume were optimized. Highly purified samples of arginine deiminase were obtained and their long-term storage conditions were selected.